Lavrentiy D.S. Legislative aspects of public-private partnership in Ukraine in sphere of healthcare - Gryshyna, Nataliia (Pressing Problems of Public Administration, 2019)
The paper explores the problem issues of forming and developing the regulatory framework for creation and implementation of the mechanisms of public-private partnership in the sphere of healthcare in Ukraine, substantiates the areas of improvement of the institutional principles for their realization and determines the factors of changing conceptual approaches to solution of the problems related to protection of the constitutional rights of the citizens of Ukraine to medical aid and access to high quality medical services